(untitled) (Journal of Nobel Medical College, 2016)
Background Percutaneous Nephrolithotomy, widely used procedure by urologists for removing renal stones nowadays. Generally, it is preferred in general anesthesia but here in our study we have compared it with spinal anesthesia to know its safety and efficacy. Material and Methods Sixty patients of either sex, aged between 20-60 years, ASA – Grade I and II, with stones size larger than 15 mm posted for Percutaneous Nephrolithotomy were randomly selected. Patient was divided in two groups 30 each, Spinal Anesthesia (S) and General Anesthesia (G). Patient’s stones sizes, numbers & location, Anesthesia duration, Surgical duration, Recovery duration, Blood loss and Blood transfusion, Analgesic demand, post-operative Nausea & Vomiting, Patient satisfaction, Hospital stays and Heart Rate and Mean arterial pressure between two groups were compared. Results There was no significant difference in terms of mean age, weight, stones sizes, and numbers and its location. The p value for Anesthesia duration and surgical duration were 0.144 and 0.22 which was insignificant. Recovery duration (p-value 0.007), Blood loss (p-value 0.004) were significantly lesser in spinal anesthesia group. There was no significant difference in nausea and vomiting, patient satisfaction when compared between two groups. But Analgesic demand, Blood Transfusion and Hospital stays significantly found to be decreased in spinal anesthesia groups (p<0.05). The mean of MAP showed no significant difference except in 10 and 20 minutes. Conclusion Spinal anesthesia tends to be as effective as general anesthesia for PCNL and beneficial in terms of recovery duration, blood loss, analgesic demands, hospital stays, hence decrease the cost of patient. Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, Page: 37-42